2008
DOI: 10.1167/iovs.08-1867
|View full text |Cite
|
Sign up to set email alerts
|

Sigma-1 Receptor Regulation of Voltage-Gated Calcium Channels Involves a Direct Interaction

Abstract: These results suggest that sigma-1 receptor activation can regulate calcium homeostasis and signaling in RGCs, likely by directly influencing the activity of L-type voltage-gated calcium channels. Regulation of calcium influx in RGCs by sigma-1 receptor ligands may represent in part the neuroprotective effect of sigma-1 receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 44 publications
5
82
0
1
Order By: Relevance
“…We focused on SOCE, but recruitment of σ1Rs to ER-PM junctions by STIM1 might also be involved in regulation of other PM channels by σ1Rs (Maurice and Su, 2009;Su et al, 2010;Kourrich et al, 2013;Pabba, 2013). For example, the L-type Ca 2+ channel is inhibited by σ1R (Tchedre et al, 2008) and by depletion of intracellular Ca 2+ stores and STIM1 (Park et al, 2010;Wang et al, 2010). We suggest that STIM1-mediated translocation of σ1R to ER-PM junctions may inhibit voltage-gated Ca 2+ entry and may also deliver σ1Rs to additional PM targets (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on SOCE, but recruitment of σ1Rs to ER-PM junctions by STIM1 might also be involved in regulation of other PM channels by σ1Rs (Maurice and Su, 2009;Su et al, 2010;Kourrich et al, 2013;Pabba, 2013). For example, the L-type Ca 2+ channel is inhibited by σ1R (Tchedre et al, 2008) and by depletion of intracellular Ca 2+ stores and STIM1 (Park et al, 2010;Wang et al, 2010). We suggest that STIM1-mediated translocation of σ1R to ER-PM junctions may inhibit voltage-gated Ca 2+ entry and may also deliver σ1Rs to additional PM targets (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…LS-1-137 (10 μM) was added to the external solution and continuously perfused through the bath for 3 min. Our previous studies have shown that the onset for the effect of σ1 receptor agonist on voltage-gated calcium channels occurs at approximately 3 min (Tchedre et al, 2008). NMDAactivated currents were recorded before (control), during LS-1-137 perfusion and after washout.…”
Section: Figurementioning
confidence: 99%
“…The S1R is a ligand-regulated non-ATP-binding membrane bound chaperone protein (Hayashi and Su, 2007). In its 125 multitasking functions, the S1R has been demonstrated to physically interact with client proteins in a functional manner including ion channels such as inositol triphosphate (IP 3 ) receptors (Hayashi and Su, 2001;Wu and Bowen, 2008), voltage-gated potassium (Aydar et al, 2002), sodium (Balasuriya et al, 2012), and calcium channels (Tchedre et al, 2008), calcium-activated chloride channels (Zhang and Cuevas, 2002), and N-methyl-D-aspartate receptors (Sircar et al, 1986b;Monnet et al, 1990;Balasuriya et al, 2013;Pabba et al, 2014). Specific interactions of the S1R with several types of G-protein coupled receptors (GPCRs) (Kim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%